2017
DOI: 10.1371/journal.pone.0184611
|View full text |Cite
|
Sign up to set email alerts
|

Long-term no-till: A major driver of fungal communities in dryland wheat cropping systems

Abstract: In the dryland Pacific Northwest wheat cropping systems, no-till is becoming more prevalent as a way to reduce soil erosion and fuel inputs. Tillage can have a profound effect on microbial communities and soilborne fungal pathogens, such as Rhizoctonia. We compared the fungal communities in long-term no-till (NT) plots adjacent to conventionally tilled (CT) plots, over three years at two locations in Washington state and one location in Idaho, US. We used pyrosequencing of the fungal ITS gene and identified 42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 56 publications
4
39
0
Order By: Relevance
“…Interestingly, microbial taxonomic 5 and functional 8 diversities in the same soil and treatments are in agreement with the results that we now report of abundance of hydrolases. Increases in fungal biomass in NT in comparison with the CT have been reported, 63 as well as differences in the strategies of C utilization, 64 and, in general, in our study, hydrolases sequences were attributed to fungi, Verticillium and Colletotrichum (lipases and laccases), and Aspergillus (proteases). Interestingly, for the amylases, sequences were attributed mainly to the archaea S. acidocaldarius ; important roles of mesophilic and thermophilic Group I archaea in soil, more specifically in N-cycling (ammonia oxidizers) have been recently described, 65 and now we extend their importance to the amylases.…”
Section: Discussionsupporting
confidence: 73%
“…Interestingly, microbial taxonomic 5 and functional 8 diversities in the same soil and treatments are in agreement with the results that we now report of abundance of hydrolases. Increases in fungal biomass in NT in comparison with the CT have been reported, 63 as well as differences in the strategies of C utilization, 64 and, in general, in our study, hydrolases sequences were attributed to fungi, Verticillium and Colletotrichum (lipases and laccases), and Aspergillus (proteases). Interestingly, for the amylases, sequences were attributed mainly to the archaea S. acidocaldarius ; important roles of mesophilic and thermophilic Group I archaea in soil, more specifically in N-cycling (ammonia oxidizers) have been recently described, 65 and now we extend their importance to the amylases.…”
Section: Discussionsupporting
confidence: 73%
“…A number of studies have found that tillage reduces total fungal biomass in agricultural soils (Helgason et al, 2009(Helgason et al, , 2010Mathew et al, 2012;Cho et al, 2017). A comparison of no-till and standard till dryland wheat found the fungal community was dominated by Ascomycota in both systems, with Ascomycota and Basidiomycota showing significant changes in the tilled system (Sharma-Poudyal et al, 2017). We also observed Ascomycota as the dominant phylum in all treatments, but it was not responsive to tillage.…”
Section: Tillage Effectsmentioning
confidence: 51%
“…It has been proposed that fungal taxa selected by conventionally tilled systems are primary colonizers of mechanically damaged plant residues and produce large numbers of tillage-resistant conidia (Sharma-Poudyal et al, 2017). Taxa more abundant in no-till are either endophytes or other groups adapted to utilizing intact roots, or taxa with extensive hyphal networks that can be disrupted by tillage (Sharma-Poudyal et al, 2017). It may be that groups that do not fall into these categories are likely to remain unaffected by the tillage regime.…”
Section: Tillage Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two most prominent cellulolytic taxa in the consortium, Cellvibrio and Chaetomium, are commonly observed in studies of agroecosystems. Cellvibrio dominated access to cellulosic C in two previous SIP studies of agricultural soils [12,35] and both Cellvibrio and Chaetomium are favored by tillage [36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%